Immunoassay detection of multiphosphorylated tau proteoforms as cerebrospinal fluid and plasma Alzheimer’s disease biomarkers - Anna L. Wojdała; Giovanni Bellomo; Lorenzo Gaetani; Charlotte E. Teunissen; Lucilla Parnetti; Davide Chiasserini (Nature Communications)
Abstract Different forms of phosphorylated tau (p-tau) have shown strong potential as Alzheimer’s disease (AD) biomarkers in both cerebrospinal fluid (CSF) and plasma. We hypothesized that p-tau proteoforms simultaneously phosphorylated at two different sites may have an increased diagnostic value compared with tau phosphorylated at a single site. Here, we developed two immunoassays detecting CSF and plasma tau simultaneously phosphorylated at both T181 and T231 (p-tau181&231) and at T217 and T231 (p-tau217&231). Subsequently, we measured CSF and plasma p-tau181&231, p-tau217&231, p-tau181, p-tau217, and p-tau231 levels in two cohorts across the AD continuum and in frontotemporal dementia (FTD) patients (discovery n = 55, validation n = 118). CSF and plasma p-tau217&231, p-tau181, p-tau217, and p-tau231 and CSF, but not plasma, p-tau181&231 were significantly elevated in all AD continuum groups vs. Neurological Disease Control group. Notably, plasma p-tau217&231 consistently showed an improved diagnostic performance compared with single-site phosphorylation assays – p-tau217 or p-tau231. The differences observed between CSF and plasma measurements suggest matrix-specific protein processing, underscoring the need for further research on the dynamics of tau phosphorylation pattern along the AD continuum.